Pengaruh Kinerja Keuangan Perusahaan dan Variabel Makroekonomi terhadap Harga Saham yang Terdaftar di Jakarta Islamic Index - Dinar Intan Mustika; Djoni Djatnika; Setiawan Setiawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to determine the effect of the company's financial performance including Debt to Equity Ratio,Return On Asset,Net Profit Margin, Earning Per Share and macroeconomic variables including GDP (Gross Domestic Income), Inflation, and BI Rate on share prices in companies listed on the Jakarta Islamic Index in 2016-2019. The type of data used is descriptive quantitative data. The sample of this study are 13 companies by using purposive sampling method. Furthermore, the data will be processed using descriptive analysis techniques and path analysis. The results of this study indicate that partially ROA, DER, and EPS have a significant positive effect on JII's stock price and NPM has no significant effect on JII's stock price. Meanwhile, the macroeconomic variable, namely GDP, Inflation, and BI Rate has no significant effect on JII's stock price.